2018
DOI: 10.2147/oaem.s160269
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving outcomes in the acute management of ischemic stroke in rural emergency departments: a quality improvement initiative in the Stroke Belt

Abstract: BackgroundThe timely evaluation and initiation of treatment for acute ischemic stroke (AIS) is critical to optimal patient outcomes. However, clinical practice often falls short of guideline-established goals. Hospitals in rural regions of the USA, and notably those in the Stroke Belt, are particularly challenged to meet timing goals since the vast majority of primary stroke centers (PSCs) are concentrated in urban academic institutions.MethodsBetween May 2015 and May 2017, emergency department (ED) teams from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…[8][9][10]22 While 9 studies involved different medical departments, 6,[10][11][12]17,19,21,22,27 15 of them concerned only Emergency departments and/or paramedics. Most of articles proposed a multimodal approach: only 7 of them concerned exclusively A&F. [7][8][9][10][11]13,22 As it's shown in Table 2, 9 articles talked about measurements for infective pathologies (especially antibiotic stewardship), 7,8,12,13,16,17,21,22,29 6 of them treated cardiac arrest or cardiovascular emergency problems, 8,19,20,[25][26][27] 2 of them treated stroke, 15,24 3 ones were about laboratory analyses 10,18,28 and 4 of them treated any other fields (diabetic ketoacidosis, use of a prothrombin complex, etc. ), (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10]22 While 9 studies involved different medical departments, 6,[10][11][12]17,19,21,22,27 15 of them concerned only Emergency departments and/or paramedics. Most of articles proposed a multimodal approach: only 7 of them concerned exclusively A&F. [7][8][9][10][11]13,22 As it's shown in Table 2, 9 articles talked about measurements for infective pathologies (especially antibiotic stewardship), 7,8,12,13,16,17,21,22,29 6 of them treated cardiac arrest or cardiovascular emergency problems, 8,19,20,[25][26][27] 2 of them treated stroke, 15,24 3 ones were about laboratory analyses 10,18,28 and 4 of them treated any other fields (diabetic ketoacidosis, use of a prothrombin complex, etc. ), (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…: increase in survival (60% vs. 35%), (12% vs 9.1%, p=0.02) 8 even after control for potential confounders and risk measures, achievement of successful reanimation by reaching the target temperature within 6 hours (25.7% vs 9.0%, p<0.00001), 25 treatment with alteplase within 60 minutes of ED arrival (1.9% vs 5.2%; p<0.01). 15 The evaluation of time-depending variables is, then, a key aspect that is also fundamental for indicators of essential assistance cares, like Italian "Essential Levels of Care", 36 which include the services that the Italian National Health Service (SSN) provides to all citizens and concerns collective prevention and public health, district assistance on the territory and hospital assistance, with also A&F.…”
Section: Reviewmentioning
confidence: 99%
“…The objective of the funding stream or “pillar” itself was to improve local performance at an individual and team level, through promoting improvements to site processes, building the relationship between rural and referral sites and evaluating health outcomes based on validated, locally-identified quality measures [ 1 ]. The overarching approach to site-level quality improvement underscoring the funding was to appreciate local context-determined needs, identified by those working in patient care, provide a broad view of safety and quality levering on the local highly functioning teams, and provide local, funded leadership to implement projects [ 19 , 20 ]. We did this through adopting a broad view of safety and quality inherent in Donabedian’s model for quality of care [ 3 ], to highlight rural team focus on ensuring safety of patients in rural and remote settings.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests a focus on quality improves providers’ clinical knowledge and competence [ 19 , 25 ] as well as patient outcomes [ 21 , 26 ]. In some studies, the quality of care has been shown to improve through facilitating more timely access to the right care by the right person in the right place [ 6 , 20 , 27 , 28 ]. Quality initiatives have also been shown to increase provider efficiency [ 7 ] and local team function [ 5 , 19 , 29 ] and increase adherence to best practice guidelines and clinical protocols [ 6 , 29 ], in some instances resulting in reduced costs [ 6 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to optimal emergency care system performance in the treatment of acute stroke include: poor public knowledge about the signs and symptoms of stroke, inadequate access to prehospital emergency care, lack of transport protocols that designate stroke centers, inadequate facility based triage, lack of timely assessment and administration of treatment, poorly resourced facilities, and inadequate financial protection for patients. Process improvements in emergency care systems have been shown to increase the proportion of ischemic strokes that receive thrombolytics [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%